Monitoring Dynamic Processes on the Earths Surface Using Synthetic Aperture Radar - Villano, Michelangelo; Krieger, Gerhard; Papathanassiou, Konstantinos P.; Moreira, Alberto (IEEE International Conference on Environmental Engineering, 2018)
Synthetic aperture radar (SAR) has proven to be a key remote sensing technique for Earth observation. However, conventional SAR systems are limited in that a wide coverage can only be achieved at the expense of a degraded resolution. Staggered SAR overcomes this limitation by means of digital beamforming and continuous variation of the pulse repetition interval (PRI). Staggered SAR is currently being considered as the baseline acquisition mode of the Tandem-L mission, whose powerful instrument will deliver weekly high-resolution global images of our planet, thereby allowing quantification of a number of essential climate variables.
Keywords: Synthetic aperture radar; Earth observation; high-resolution wide-swath imaging; Tandem-L; staggered SAR; frequent monitoring.